Japan: the harbinger state. (23rd March 2023) - Lipscy, Phillip Y.
Abstract: Why study Japan? Research on contemporary Japanese politics and foreign policy faces headwinds from the relative geopolitical decline of Japan and scholars skeptical about single-country studies. An overview of Japanese politics publications in English-language journals over the past four decades suggests the subfield remains active and robust. However, there is still room to grow. I argue that Japan is a harbinger state, which experiences many challenges before others in the international system. As such, studying Japan can inform both scholars and policymakers about the political challenges other countries are likely to confront in the future. In turn, scholarship on Japan offers a critical opportunity to develop theoretical insights, assess early empirical evidence, and offer policy lessons about emerging challenges and the political contestation surrounding them. I consider the reasons why Japan so often emerges as a harbinger across issue areas and suggest areas for ongoing scholarly attention.